2011
DOI: 10.1017/s0007114511002042
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of antisecretory factor-rich egg yolk on the late phases of 2,4,6-trinitrobenzenesulphonic acid colitis in mice

Abstract: Antisecretory factor (AF) is expressed in all tissues of mammals, inhibits intestinal hypersecretion and has anti-inflammatory properties as well. Endogenous AF synthesis may be stimulated by feeding hydrothermally processed cereals. Alternatively, freeze-dried egg yolk can be used as a source of exogenous AF. Several reports have suggested that AF from freeze-dried egg yolk may be useful in inflammatory bowel disease. We assessed the effect of freeze-dried, AF-rich egg yolk intake on 2,4,6-trinitrobenzenesulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In addition to electrolyte and water transport regulation, AF acts by counteracting various forms of inflammatory reactions [ 21 23 ]. AF has also been demonstrated to modulate the proliferation of memory/effector T cells, thereby inhibiting the severity of experimental autoimmune encephalitis [ 24 , 25 ], and to inhibit the extent of inflammation in the late phase of a mouse colitis model [ 26 ]. Furthermore, we have shown that intranasal application of AF-16 suppressed an elevated ICP and completely abolished the mortality in rats with encephalitis experimentally induced by herpes simplex virus (HSV-1) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to electrolyte and water transport regulation, AF acts by counteracting various forms of inflammatory reactions [ 21 23 ]. AF has also been demonstrated to modulate the proliferation of memory/effector T cells, thereby inhibiting the severity of experimental autoimmune encephalitis [ 24 , 25 ], and to inhibit the extent of inflammation in the late phase of a mouse colitis model [ 26 ]. Furthermore, we have shown that intranasal application of AF-16 suppressed an elevated ICP and completely abolished the mortality in rats with encephalitis experimentally induced by herpes simplex virus (HSV-1) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNBS-induced inflammation generates transmural colonic lesions [ 13 ] that share the hallmarks of human CD [ 14 ]. Severe colitis after TNBS enema is followed by body weight loss, diarrhea, and increased myeloperoxidase (MPO) activity in wild-type mice [ 10 , 15 , 16 ]. On the other hand, DSS acute colitis is usually induced by continuous administration of 2–7% DSS in drinking water for a short period.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat and other cereal grains contain both inflammatory substances such as agglutinins and anti-inflammatory substances such as antioxidants [13]. Malting increases the levels of anti-inflammatory substances in cereals by releasing these substances from larger complexes [46], and so intake of extensively malted oats and wheat can counteract enterotoxic diarrhea and inflammatory bowel disease such as ulcerous colitis and Crohn’s disease [79]. The active phytochemicals seem to be certain phenols which induce an antisecretory factor (AF) in the blood [10].…”
Section: Introductionmentioning
confidence: 99%